1989
DOI: 10.1104/pp.89.4.1117
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Actively Filling Sucrose Sinks

Abstract: ABSTRACTpropose that they should be more correctly termed sucrolysis and sucroneogenesis. Before recent work it was customary to assume that sucrose synthase action resulted in the formation of UDP-glucose and then other nucleotide sugars leading into sugar polymer synthesis, such as plant cell walls. However, a substrate level pool of PPi was measured in plants (2,7,27), and we successfully tested the pyrophosphorolysis of UDPglucose feeding glucose 1-P directly into plant metabolism (32). These steps are an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
4

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(133 citation statements)
references
References 31 publications
5
124
0
4
Order By: Relevance
“…High sucrose synthase activity may lead to reduced concentrations of sucrose in pericarp cells and increased sucrose gradient from the source leaves to the fruit, resulting in greater sink strength (Walker et al, 1978). Severa1 authors (Claussen et al, 1986;Sung et al, 1989) have suggested that the activity of sucrose synthase could be used as a biochemical marker for sink strength. Consistent with this suggestion, we observed that, at 65 d after germination, the young fruit had the highest level of sucrose synthase activity (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…High sucrose synthase activity may lead to reduced concentrations of sucrose in pericarp cells and increased sucrose gradient from the source leaves to the fruit, resulting in greater sink strength (Walker et al, 1978). Severa1 authors (Claussen et al, 1986;Sung et al, 1989) have suggested that the activity of sucrose synthase could be used as a biochemical marker for sink strength. Consistent with this suggestion, we observed that, at 65 d after germination, the young fruit had the highest level of sucrose synthase activity (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…At this date, SuSy activity was higher than in other shoot organs. Since SuSy is considered a good indicator of the sink strength of an organ [24], the shoot apex on the 2nd day of the flush appears therefore to be the strongest sink of the shoot. This fact is supported by the non-vascular localization of SuSy protein observed here.…”
Section: Apexmentioning
confidence: 99%
“…A positive correlation between sucrose synthase activity, sink strength and sucrose import has been demonstrated in many sink organs, suggesting a role for this enzyme in carbohydrate partitioning between sink and source organs [24,28,30]. In addition, SuSy appears to play a key role in supplying energy for loading and unloading in phloem by providing substrate for respiration [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, therefore, significant that the enzyme sucrose synthase has recently been shown to play a major role in determining the sink strength of storage organs which accumulate starch as a major reserve (12).…”
Section: Active Versus Passive Phloem Unloadingmentioning
confidence: 99%